Monoclonal antibodies in cervical malignancy-related HPV - Aghbash, Parisa Shiri; Hemmat, Nima; Fathi, Hamidreza; Baghi, Hossein Bannazadeh (Frontiers in Oncology, 2022)
Despite many efforts to treat HPV infection, cervical cancer survival is still poor for several reasons, including resistance to chemotherapy and relapse. Numerous treatments such as surgery, radiation therapy, immune cell-based therapies, siRNA combined with various drugs, and immunotherapy are being studied and performed to provide the best treatment. Depending on the stage and size of the tumor, methods such as radical hysterectomy, pelvic lymphadenectomy, or chemotherapy can be utilized to treat cervical cancer. While accepted, these treatments lead to interruption in cellular pathways and immune system homeostasis. In addition to a low survival rate, cervical neoplasm incidence has been rising significantly. However, new strategies have been proposed to increase patient survival while reducing the toxicity of chemotherapy, including targeted therapy and monoclonal antibodies. In this article, we discuss the types and potential therapeutic role of monoclonal antibodies in cervical cancer.